Handmade holiday festive embroidery patterns and techniques for Christmas crafting - Ploof, Alyssa (Rocky Nook, 2024)
For fun, festive holiday décor and homemade gifts, look no further than Handmade Holiday: Festive Embroidery Patterns and Techniques for Christmas Crafting! With this book of lovely Christmas embroidery scenes, designed by professional needlework artist Aly Ploof, you can add a touch of holiday spirit to napkins, towels, garments, and other textiles. Embroidery is an age-old needlework skill that has been entertaining crafters and makers for generations. There's nothing more relaxing on a frosty winter evening than painting with thread, so grab your cup of cocoa and settle in by the fire. Handmade Holiday offers 16 patterns to make your Christmas crafting merry and bright-as well as chapters on techniques for beginners, and a stitch library for easy reference. Whether you're a beginner interested in learning a new craft, or an experienced embroiderer looking to create one-of-a-kind handmade gifts, this book has patterns you'll love. Celebrate the season with Handmade Holiday!
Keywords: Embroidery -- Patterns; Christmas decorations; Broderie; Modèles; Décorations de Noël